Analysis of the low-molecular weight antioxidants of transgenic plants Nicotiana tabacum under abiotic stress conditions - Pristupa, Kristina V.; Kukulianskaya, Tatsiana A.; Khramtsova, Elena A. (Experimental Biology and Biotechnology, 2020)
We conducted a comparative analysis of biochemical parameters of non-transgenic and transgenic Nicotiana tabacum, plants cultivated in heavy metal polluted soils. Transgenic plants had in their genome a bacterial acdS-gene encoding the 1-aminocyclopropane-1-carboxylate deaminase (ACC-deaminase) enzyme. The introduction of elevated concentrations of copper, chromium, and lead ions into the soil promotes induction of the acdS-gene expression and an increase in ACC-deaminase activity in transgenic plants. It was shown that the content of phenolic compounds (flavonoids), ascorbic acid, the total antioxidant activity of plants increased under abiotic stress.